Rancang Bangun Sistem Absensi Pegawai Berbasis RFID di PT. Bina Nelayan Jaya Kota Sorong - Ery Murniyasih; Wennie Mandela; Luluk Suryani; Stefany Margareta Martono (Electro Luceat, 2026)
Employee attendance is an essential aspect of maintaining work discipline and managing human resources within an organization. Manual attendance recording may lead to recording errors and delays in attendance information management. This study aims to design and implement an employee attendance system based on Radio Frequency Identification (RFID) and the Internet of Things (IoT) at PT. Bina Nelayan Jaya, Sorong City. The study employed the Research and Development (R&D) method, which consisted of needs analysis, system design, implementation, and functional testing using the black-box testing method. The proposed system integrates an MFRC522 RFID module as the card reader, an Arduino Mega 2560 as the main controller, a NodeMCU ESP8266 for wireless data communication via a Wi-Fi network, and a web-based application for attendance data management. The testing results indicated that all primary system functions operated according to the functional requirements, achieving a 100% success rate. The system successfully read RFID cards, transmitted attendance data to the database, managed employee records, and displayed attendance information on a web-based dashboard in real time. The developed system facilitates a more efficient and computerized attendance process while simplifying attendance data management at PT. Bina Nelayan Jaya, Sorong City.